Utilizing PBPK Modeling to Evaluate the Potential of a Significant Drug–Drug Interaction Between Clopidogrel and Dasabuvir: A Scientific Perspective. Issue 4 (26th April 2017) - Arya, V; Zhao, P; Reynolds, KS; Mishra, P; Younis, IR
Abstract : Dasabuvir, a component of VIEKIRA PAK, is a substrate of CYP2C8 enzymes. Prescribing information for VIEKIRA PAK contraindicates gemfibrozil, a strong CYP2C8 inhibitor, because coadministration significantly increases dasabuvir exposures, which may increase the risk of QT prolongation. Clopidogrel may increase dasabuvir exposures primarily due to CYP2C8 inhibition by clopidogrel‐acyl‐β‐D‐glucuronide. This commentary outlines the US Food and Drug Administration (FDA) interdisciplinary review team's scientific perspective to address the potential for a significant drug–drug interaction (DDI) between clopidogrel and VIEKIRA PAK.